PWE-353 Determining the sensitivity and specificity of annual faecal immunochemical tests for haemoglobin (FIT) compared with findings at surveillance colonoscopy for patients diagnosed with intermediate risk adenomas – the fit for follow-up study. (22nd June 2015) - MacRae, E; Marchevsky, N; Brenner, A; Patel, B; Pearson, S; Piggott, C; von Wagner, C; Wardle, J; Halloran, S; Atkin, W
Abstract : Introduction: Patients diagnosed with intermediate-risk adenomas following a positive guaiac faecal occult blood test in the English NHS Bowel Cancer Screening Programme (BCSP) are invited to attend a surveillance colonoscopy after three years. As demand for colonoscopy services increases, effective non-colonoscopic approaches to surveillance are needed. The FIT for Follow-Up study aims to determine the programme sensitivity and specificity of three annual faecal immunochemical tests for haemoglobin (FIT) in detecting advanced adenomas (AA) and/or colorectal cancers in patients undergoing surveillance, compared with findings at the gold standard colonoscopy. Method: Eligible participants are invited to complete annual FIT tests (OC-SENSOR, Eiken Chemical Co. Ltd) whilst awaiting their surveillance colonoscopy. If a FIT is positive (≥40μg Hb/g faeces) participants are offered an earlier surveillance colonoscopy. If a FIT is negative participants are offered further annual FIT tests and their original three year surveillance colonoscopy. Results: Recruitment to the study began in January 2012. In round 1, 8009 eligible patients were invited to participate, 74% (5925) consented and returned a valid FIT kit, and the positivity rate was 5.8% (346/5925). Of the FIT positive participants, 88.2% (305/346) attended an earlier colonoscopy, 23.9% (73/305) had AA and 1.9% (6/305) were diagnosed with cancer. In round 2, 5510 participants were invited to complete a FIT, 96.9% (5340/5510) returned a valid kit, and the positivity rate was 4.5% (239/5340). Of the FIT positive participants, 81.2% (194/239) attended an earlier colonoscopy, 16.5% (32/194) had AA and 4.1% (8/194) were diagnosed with cancer. Round 3 of the study is now underway. To date, 3118 participants have been invited to complete a FIT, 93.0% have returned a valid kit (2900/3118), and the positivity rate is 4.0% (117/2900). All participants in round 3 are invited to attend colonoscopies: earlier if they are positive, three year surveillance exams if they are negative. Attendance rates at round 3 colonoscopies are currently over 80% and we have collected 984 colonoscopy reports from 62 screening centres. Conclusion: We have experienced a very high response and retention rate in all rounds of the study. We are now focused on encouraging participants to attend their surveillance colonoscopies, and collecting reports from screening centres, to maximise the benefits to the study of the high uptake rates achieved to date. Disclosure of interest: None Declared.